2010
DOI: 10.1246/cl.2010.978
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Two-stepped Spin Transitions Induced by Intramolecular Electron Transfers in a Cyanide-bridged Molecular Square

Abstract: A cyanide-bridged molecular square, [Co 2 Fe 2 (CN) 6 (tp*) 2 -(dtbbpy) 4 ](PF 6 ) 2 ¢2MeOH (1) (tp* = hydrotris(3,5-dimethylpyrazol-1-yl) borate and dtbbpy = 4,4¤-di-tert-butyl-2,2¤-bipyridine) was prepared by the reaction of (Bu 4 N) [Fe(CN) 3 (tp*)] with Co(CF 3 SO 3 ) 2 ¢6H 2 O and dtbbpy in methanol. Variable temperature X-ray structural analyses, magnetic and spectroscopic data revealed that 1 exhibited novel thermal two-stepped spin transitions induced by intramolecular electron transfers.Prussian blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…The latter, in unbuffered aqueous solution, shows two redox waves with close potentials; the two iron centers (590 and 710 mV) are not equivalent, despite having very similar reduction potentials (see Figure b, solid line). The separation of 50–60 mV between the two anodic and cathodic peaks confirms one electron processes, and the separation between the two signals (120 mV) produces a comproportionation equilibrium constant of 1×10 2 , comparatively small when compared to the values for similar mixed valence complexes . The positive shifts of the potential with respect to free hexacyanidoferrate are consistent with inductive effects of the Co III moieties attached to the center.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…The latter, in unbuffered aqueous solution, shows two redox waves with close potentials; the two iron centers (590 and 710 mV) are not equivalent, despite having very similar reduction potentials (see Figure b, solid line). The separation of 50–60 mV between the two anodic and cathodic peaks confirms one electron processes, and the separation between the two signals (120 mV) produces a comproportionation equilibrium constant of 1×10 2 , comparatively small when compared to the values for similar mixed valence complexes . The positive shifts of the potential with respect to free hexacyanidoferrate are consistent with inductive effects of the Co III moieties attached to the center.…”
Section: Methodssupporting
confidence: 57%
“…The separation of 50-60 mV between the two anodic and cathodic peaks confirmso ne electron processes, and the separation between the two signals (120 mV) produces ac omproportionation equilibrium constanto f1 10 2 ,c omparatively small when compared to the values for similar mixed valencec omplexes. [12,48,66] The positive shifts of the potential with respect to free hexacyanidoferrate [67] are consistent with inductive effectso ft he Co III moieties attached to the center.I nterestingly,w hen the same electrochemical experiment is carried out in 2 m HClO 4 ,t he two signals of the iron center coalesce with acathodic-anodic signalseparationofapproximately 100 mV at 815 and 910 mV (Figure 1b,d ashed line). It is clear that, on sequential protonation of the terminal cyanidol igands, the two iron centers become formally equivalent owing to positive induction caused by the change to Fe II -CNH groups,and the comproportionation equilibrium constant is drastically reduced.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…However, the Oshio group recently reported the first example of an ETCST-active complex that showed two-step behavior, and a metastable intermediate state. [49] An X-ray structural analyses conducted at temperatures corresponding to the IM and HT phases showed that the crystallographic space groups remained the same (C2/c), but that the bonding distances around the metal ions changed markedly. In the HT phase the Co and Fe ions had average bonding distances of 2.113 and 1.964 Å, respectively, suggesting complete ETCST from the LT phase to the HT phase.…”
Section: Electron-transfer-coupled Spin Transitionmentioning
confidence: 99%
“…The observed broad thermal hysteresis of 18 K reveals the first‐order phase transition associated with the electron‐transfer process. Another important result was reported by Oshio and co‐workers, who used the compound {[(Tp*)Fe III (CN) 3 ] 2 [Co II (dtbbpy) 2 ] 2 }[PF 6 ] 2 · 2MeOH (dtbbpy = 4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridine) to demonstrate the possible transfer of the electron‐transfer phenomenon and the associated properties from the solid state to solution , . Recently, the dinuclear cyanide‐bridged [{(Tp)Fe(CN) 3 }{Co‐(PY5Me 2 )}][CF 3 SO 3 ] (Tp = tripyrazolylborate) complex was obtained and demonstrated to exhibit charge‐transfer‐induced electron transfer .…”
Section: Introductionmentioning
confidence: 93%